Perceptual and objective evaluation of speech processed by adaptive differential pcm - McDermott, B.; Scagliola, C.; Goodman, D. (Bell System Technical Journal, 1978)
An experiment has been performed to study the perceptual characteristics of speech processed by adaptive differential PCM. We created 18 three-bit and four-bit coders spanning a wide range of quantizer adaptation parameters. Subjects judged differences between coders and rated the quality of each coder individually. The difference data reveal three important perceptual characteristics: overall clarity, signal vs. background degradation, and rough vs. smooth impairment. These characteristics are strongly correlated with coder design parameters and objective performance measures. Overall subjective quality is well predicted by segmental signal-to-noise ratio and even better by a linear combination of measures of granular distortion and overload distortion.